Thyrotoxic periodic paralysis: A case report - AlMoteri, Barakat Lafi G.; Aslam, Mohammad (International Journal of Health Sciences, 2017)
Thyrotoxic periodic paralysis (TPP) is a rare complication of hyperthyroidism characterized by episodes of muscle weakness and hypokalemia. TPP is typically present in young Asian men, female and non-Asian ethnic group can also be affected. TPP is a curable cause of hypokalemic periodic paralysis, can often be the first manifestation of thyrotoxicosis. Factors like high carbohydrate diet, strenuous exercise, emotional stress and steroid can precipitate an attack of TPP. The presence of both hypokalemia and elevated level of thyroxine (T4) and triidothyronine (T3) are important diagnostic features during the acute episode. Treatment of TPP involves 2 steps, immediate action to reverse the paralysis by correction of hypokalemia followed by measures to prevent future attacks by restoration of a euthyroid state. We report a first case of TPP, which was delayed to diagnose, from our hospital due to Graves’ disease in Asian man who present with second episode of paralytic attack before the diagnosis was made which is also unusual as attacks were not frequent.